Identification of Quantifiable Hemodynamic Factors in the Assessment of Cerebral Aneurysm Behavior On behalf of the Subcommittee on Biorheology of the Scientific and Standardization Committee of the ISTH - Burleson, Arrmelle C; Turitto, Vincent T (Thrombosis and Haemostasis, 1996)
Previous experimental and theoretical studies on the hemodynamics of saccular intracranial aneurysms have provided evidence that aneurysms tend to grow, thrombose and rupture when (1) wall shear stress and mural tension are increased compared to normal values, and (2) flow deviates from a laminar unidirectional pattern (for example flow recirculation). Aneurysm wall shear stress, however, is the only hemodynamic factor which has received special attention in terms of estimation. Additional flow-related parameters exist which could potentially bring increased insight into mechanisms for cerebral aneurysm behavior; they could also help categorize the severity of such malformations and design effective intravascular treatment techniques. The purpose of this paper is thus to present an overview of such hemodynamic factors that could assist in determining the geometries which present the greatest risks to patients. These parameters include (1) hemodynamic shear stress, (2) pressure and related stresses, (3) impingement force on the aneurysm wall, (4) inflow rate into the aneurysm, and (5) residence time of blood within the aneurysmal sac. In addition, these factors can also be currently estimated in an in vitro setting.